2011
DOI: 10.1002/cyto.b.20587
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the cellular and humoral immune response to pediatric open heart surgery by methylprednisolone

Abstract: Background: With the intention to reduce overshooting immune response, glucocorticoids are frequently administered perioperatively in children undergoing open heart surgery. In a retrospective study we investigated extensively the modulation of the humoral and cellular immune response by methylprednisolone (MP).Methods: This study was carried out on blood samples from two groups of children who had undergone surgical correction of atrial or ventricular septal defects, either without (MP 2 , n 5 10), or with MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 58 publications
2
15
1
1
Order By: Relevance
“…S2, 3). Consistent with previous reports (11, 13, 15, 16, 34), surgery induced a 1.2-fold (±0.06, q<0.01) expansion of neutrophils 1 h after surgery, a 1.9-fold (±0.19, q<0.01) expansion of CD14 + MCs at 24 h, and a contraction of CD4 + and CD8 + T cells to 0.77-fold (±0.07, q<0.01) and 0.71-fold (±0.07, q<0.01), respectively, at 24 h (Fig. S3).…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…S2, 3). Consistent with previous reports (11, 13, 15, 16, 34), surgery induced a 1.2-fold (±0.06, q<0.01) expansion of neutrophils 1 h after surgery, a 1.9-fold (±0.19, q<0.01) expansion of CD14 + MCs at 24 h, and a contraction of CD4 + and CD8 + T cells to 0.77-fold (±0.07, q<0.01) and 0.71-fold (±0.07, q<0.01), respectively, at 24 h (Fig. S3).…”
Section: Resultssupporting
confidence: 94%
“…Consistent with previous studies (11, 13–15, 34, 47), innate immune cells expanded soon after surgery, followed by a reduction of cells within the adaptive branch (Fig. 3).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Some studies found that steroids can blunt inflammation [7][8][9][10][11][12][13][14] while others found the opposite [15]. Most importantly, it is unclear to what degree this presumed Banti-inflammatoryê ffect also translates into better clinical outcomes [7,10,13].…”
Section: Less Inflammation Better Clinical Outcomes?mentioning
confidence: 99%